Impact of employee psychological empowerment, process and equipment on operational service quality in the oilfield service industry - Onyemeh, Ngozi C. (2017)
This study examines the impact of employee psychological empowerment, process and equipment maintenance on operational service quality in the oilfield service industry. With services ranging from exploration to downstream activities including supply of personnel, and products such as crude oil, natural gas and refined products, the oilfield operations presents unique operational quality challenges. Measured mostly in terms of non-productive time, the success and failure of operations have necessitated a focus on personnel, equipment maintenance and process by researchers. However, with diminishing reserves, fluctuating product demand and stringent laws and regulations, organizations seek to optimize resources and strategically invest on the factor(s) with significant potential to reduce non-productive time, and subsequently improve quality and efficiency. This study therefore, adopting a mixed method approach, aims to determine which factor(s) are significantly associated with quality to aid this strategic focus and investment.